Scenicite, a new uranyl-sulfate mineral from the White Canyon district, San Juan County, Utah, USA. (30th October 2022) - Kampf, Anthony R.; Plášil, Jakub; Olds, Travis A.; Ma, Chi; Marty, Joe
Abstract: The new mineral scenicite (IMA2021-057), [(UO2 )(H2 O)2 (SO4 )]2 ⋅3H2 O, was found in the Green Lizard, Giveaway–Simplot, Markey and Scenic mines, White Canyon district, San Juan County, Utah, USA, where it occurs as a secondary phase on granular quartz matrix in association with various combinations of deliensite, gypsum, natrozippeite, rietveldite and shumwayite. Scenicite crystals are transparent, light green yellow, poorly formed blades or prisms, up to 0.1 mm in length. The mineral has white streak and vitreous lustre. It exhibits bright greenish-white fluorescence (405 nm laser). It is brittle with irregular, curved fracture and a Mohs hardness of ~2. It has excellent {100} and good {001} cleavages. The calculated density is 3.497 g cm –3 . Optically, the mineral is biaxial (–) with α = 1.556(2), β = 1.573(2), γ = 1.576(2) (white light); 2V = 45(3)°; extreme r < v dispersion; orientation: X = c, Y = a, Z = b ; pleochroism: X and Y = colourless, Z = light green–yellow; and X = Y < Z . The Raman spectrum exhibits bands consistent with UO2 2+, SO4 2– and O–H. Electron microprobe analysis provided the empirical formula U1.996 S2.005 O19 H13.997 . The five strongest powder X-ray diffraction lines are [ d obs Å( I )( hkl )]: 7.69(70)(201), 5.63(100)(111), 4.92(84)(202, 310), 4.80(93)(401) and 3.398(55)(020, 120, 511, 601). Scenicite is orthorhombic, Pca 21, a = 21.2144(15), b = 6.8188(3) c = 11.2554(6) Å, V = 1628.18(16) Å 3 and Z = 4. In the structure of scenicite ( R 1 = 0.0365 for 1259 I > 2σ I ), linkages of pentagonal bipyramids and tetrahedra form an infinite neutral [(UO2 )(SO4 )(H2 O)2 ] chain. The structure of shumwayite contains topologically identical chains.